Physical Rehabilitation in Minor Traumatic Injury or Concussion - Sharma, Vivek; DeMatteo, Carol; Arora, Himanshu (Indian Journal of Neurotrauma, 2017)
Concussion is a traumatic brain injury and can be caused by sports and non-sports related injuries. Most patients recover completely within days to several weeks; but, some patients continue to experience postconcussion symptoms including but not limited to headache, dizziness and neck pain. The mainstay of treatment for concussion in sports has been physical and cognitive rest until the acute symptoms abates. However, the window period for rest is currently being debated. For patients with persisting symptoms, longer than 1 month, multidisciplinary team approach is advisable. There is emerging evidence for the role of physical therapy as a treatment option in this population, especially for postconcussion symptoms.
Keywords: concussion; mild traumatic brain injury; physical rehabilitation; physiotherapy